Swim Training Improves HOMA-IR in Type 2 Diabetes Induced by High Fat Diet and Low Dose of Streptozotocin in Male Rats - Rafigheh Ghiasi; Farhad Ghadiri Soufi; Mohammad hossein Somi; Gisou Mohaddes; Fariba Mirzaie Bavil; Roya Naderi; Mohammad Reza Alipour (Tabriz University of Medical Sciences, 2015)
Purpose: Insulin resistance plays a key role in the onset and development of type 2 diabetes mellitus (T2DM) and its complications. In this study, we evaluated the effect of swim training on insulin resistance in diabetic rats. Methods: Forty male Wistar rats were randomly divided into four groups (n=10): sedentary control (Con), sedentary diabetic (Dia), swim trained control (Exe) and swim trained diabetic (Dia+Exe) rats. Diabetes was induced by high fat diet (HFD) and a low dose of streptozotocin (35 mg/kg, i.p). In trained groups, one week after the induction of diabetes, animals were subjected to swimming (60 min/5 days a week) for 10 weeks. At the end of training, fasting blood sugar (FBS), oral glucose tolerance test (OGTT), fasting/basal insulin, glycosylated hemoglobin (HbA1c) levels, insulin resistance index, homeostasis model assessment method (HOMA-IR), triglycerides (TG,) total cholesterol (TCh), and high density lipoprotein (HDL) levels in blood were measured. Results: Swimming significantly improved OGTT (P<0.01) and HOMA-IR (P<0.01). Swim training also significantly decreased FBS (p<0.01), fasting/basal insulin (P<0.01), HbA1C (p<0.01), TG (P<0.05), and TCh (P<0.05) levels. It also significantly increased HDL (p<0.05) level. Conclusion: Our findings indicate that swim training improved glycemic control and insulin sensitivity in type 2 diabetes caused by high fat diet in male rats.